Meningkatkan Karakter Disiplin Melalui Metode Pembiasaan Pada Anak Usia Dini - Intan Sutrawati; Baik Nilawati Astini; Ika Rachmayani; Nurhasanah Nurhasanah (Indonesian Publication Center, 2023)
This research aims to improve discipline character through habituation methods in early childhood. This type of research is Classroom Action Research (PTK). The subjects of this research were 9 students from group A. The data collection methods used are observation and documentation. Data analysis techniques use qualitative descriptive and quantitative descriptive. The results of the research show that the habituation method can improve the discipline character of children. The research results after implementing the habituation method carried out by the teacher in cycle 1 obtained a percentage of 55.66%, including the good category, which then increased in cycle II with a percentage of 92% and was categorized as Very good. By increasing the application of the habituation method, the discipline character of group A in cycle 1 received a percentage of 60.56%, including the good category, and increased in cycle II to reach a percentage of 88.35% in the very good category, so that it had reached a success percentage of 85%. Based on the results of this research, it can be concluded that the application of the habituation method can improve the disciplinary character of children in group A of the Tanak Kaken Islamic Kindergarten.